The effect of the amyloid-beta peptide on the fluidity of cell membranes : a study by fluorescence correlation spectroscopy - Ng, Justin Wei Qing (2017)
Alzheimer’s disease (AD) is an age-related neurodegenerative disease which affects up to 80% of patients presenting dementia. One of the key factors thought lead to AD is the aggregation of the amyloid-beta (Aβ) in susceptible brain regions, namely the cerebral cortex and hippocampus. Aβ is thought to interact with the cell membrane, perturbing its structure and organization, thus changing the fluidity and normal function of the cell membrane, leading to detrimental effects on the cells. Although there have been several studies done regarding this topic, the results have been conflicting and thus inconclusive, likely due to the drawbacks and biases introduced by techniques used in those studies. We therefore sought to find a conclusive answer to the question of whether Aβ affects cell plasma membrane fluidity. To this end, we used imaging TIRF-fluorescence correlation spectroscopy (ITIR-FCS) to make measurements of fluidity of one bulk membrane probe, DiI, and two ordered/raft-type membrane probes, a transiently expressed GPI-linked GFP and cholera toxin subunit B, on the membranes of living cells that were exposed to Aβ. Three cell lines – SH-SY5Y human neuroblastoma, U87 human glioma and Neuro-2a mouse neuroblastoma – were selected for our study based on their origin in brain tissue and previous use in Aβ-related studies. We found that Aβ did not change the fluidity of bulk and raft-type membranes of these cells, even though the concentration of Aβ administered was sufficient to trigger acute programed cell death (apoptosis). The reason for this negative response is yet unclear, and we do not rule out the possibility that Aβ exposure may induce changes in membrane fluidity under other conditions, such as in vivo and in AD patients, through complex mechanisms such as altered lipid metabolism. We also note the following limitations of our study – 1) because there was no solution-based assaying of the Aβ content, the exact composition of the Aβ solution is unknown; 2) the number and type of membrane probes used is not totally comprehensive; 3) there may be changes to the membrane that are too subtle or complex to be measured by standard ITIR-FCS and 4) our method of Aβ treatment represents an acute, high-dose exposure of cells to Aβ and may not be representative of what happens in the natural AD disease progression. While our observations do not agree with several earlier studies, to our knowledge, ours is the first study examining the effect of Aβ on membrane fluidity of living cells. We thus believe and conclude that within the parameters examined in this study, we have shown that exposing cells to Aβ does not result in changes in membrane fluidity in the short term, even at Aβ concentrations that are sufficient to kill the cells. This information may be of help to researchers planning studies investigating the effects of Aβ on the cell membrane.